Two Decades of Research on Government Funded Health Insurance in India (2007–2025): A Bibliometric Analysis of PM‐JAY and Related Schemes - Sagar Pandey; Pushpender Yadav (World Medical & Health Policy, 2026)
ABSTRACT Government‐funded health insurance (GFHI) has become a central component of India's health financing strategy, generating substantial research across public health, health policy, and health systems. However, there is a need to comprehensively map the intellectual evolution of this field. This study conducted a bibliometric analysis using records of publications from Scopus and Web of Science core collection databases. After screening, deduplication, and application of predefined eligibility criteria, a total of 388 publications published between 2007 and 2025 were included. Bibliomterix package in R and VOSviewer were used to evaluate publication trends, citation performance, authorship patterns, collaboration networks, source productivity, thematic evolution, and keyword co‐occurrence. The sustained growth along with annual rate of 27.82% reflects the emerging interest in this field. India emerged as the leading contributor, supported by increasing international collaborations. Thematic analyses reveal an evolution form early research on insurance coverage, health financing, governance, strategic purchasing, digital health, and health system strengthening. Research on GFHI in India has expanded rapidly over the past two decades and has evolved into multidisciplinary field. This analysis provides comprehensive evidence maps that identifies influential contributors, emerging themes of research, and knowledge gaps, offering valuable guidance for scholars, funding agencies, and policymakers involved in strengthening health financing and advancing UHC in India.